A novel method to analyze 5‐hydroxymethylcytosine in CpG sequences using maintenance DNA methyltransferase, DNMT1. Issue 1 (8th September 2015) - Takahashi, Saori; Suetake, Isao; Engelhardt, Jan; Tajima, Shoji
Abstract : Hydroxymethylcytosine has been shown to be involved in DNA demethylation and gene expression. Although methods to determine the position of hydroxymethylcytosine at single‐base resolution have been reported, these methods involve some difficulties. Here, we report a simple method to analyze hydroxymethylcytosine in the CpG sequence utilizing the maintenance DNA methylation activity of DNMT1, which selectively methylates hemi‐methylated but not hemi‐hydroxymethylated CpG sequences. The method enables monitoring of the dynamics of the hydroxymethylation state of a specific genome site. Abstract : We have developed a novel method to determine 5hmC in CpG sequences. The method uses the DNA methylation activity of DNMT1. The method can be applied to about 90% of the mouse and human genomes. Dynamic changes in 5hmC and 5mC were successfully monitored.